S132. SAMPLING BIAS IN STUDIES OF FIRST-EPISODE PSYCHOSIS – A FOLLOW-UP STUDY. (18th May 2020) - Walta, Maija; Laurikainen, Heikki; Armio, Reetta-Liina; From, Tiina; Salokangas, Raimo K R; Hietala, Jarmo
Abstract: Background: Attrition rates and sampling bias in controlled clinical studies are a concern when evaluating the relevance of the results to a specific patient population in a real-life clinical / treatment setting. Dropout rates in studies on psychotic disorders are high and many eligibility criteria may lead to bias in study samples. We wanted to analyze how representative are the patient samples typically included in first-episode psychosis studies such as the Turku Early Psychosis (TEPS) study by using a platform of 3772 consecutive admissions to clinical psychiatric services of Turku Psychiatry. Methods: TEPS study was started in 2011 as a part of a larger study on psychosis treatment processes in Turku Psychiatric services. Each patient, inpatient and outpatient, went through initial clinical screening by the treatment group which was followed by a structured evaluation if the screen for first-episode psychosis was positive. Between Oct 2011 and June 2016 there were 195 patients with first-episode psychosis (FEP) suitable to the TEPS study. Of them 102 were willing and 93 were not willing to participate or were not reached in a baseline structured evaluation. Using patient records, we compared if these two groups differed in terms of clinical variables, treatment or prognosis during a 1-year follow-up. Time of hospital stay, involuntary vs. voluntary admission, coercive measures during the hospital care, re-hospitalizations and drop-out from the clinical care during the follow-up were used as outcomes. Results: Non-participating (NTP) group had higher rate of involuntary care than participating (TP) group (70 % vs 62 %) as well as higher rate of coercion during the treatment and higher rate of re-admissions during the follow-up than the TP group (36 % vs 22 % and 41 % vs 34 %, respectively) but these differences did not reach statistical significance. During the one-year follow-up NTP group had a significantly higher rate of dropping out from the clinical care than participating TP group (48 % vs 30 %, p=0.01). NTP group had also higher rate of dropping out of clinical treatment mainly because of patient non-adherence (33 % vs 16 %, p=0.03). Discussion: Nearly half (47 %) of the intent-to-study FEP patients were not reached or declined to participate in our study. Non-participating patients had a slightly more severe illness and poorer treatment adherence during one-year follow-up. The clinical differences were not as marked as we expected. E.g. involuntary care, inpatient care and more coercion during the follow-up were not significantly different between NTP and TP groups. Nevertheless, the data suggest considerable differences between participating and non-participating patients with first-episode psychosis which should be taken in to account when evaluating the generalizability of the results for an unselected group of psychotic patients in 'real-life' clinical care.